Patriotism and solidarity in the west and in Russia - Grigoryevich Volkov, Yury; Vladimirovna Vereshchagina, Anna; Vladimirovich Lubsky, Anatoly; Olegovna Vagina, Viktoriya; Viktorovich Gubarev, Ivan (International Journal of Engineering and Technology, 2018)
The article considers the peculiarities of the formation and development of patriotism and solidarity in the West and in Russia. The nature of these phenomena is revealed from the point of view of their socio-cultural and historical dependence. The article analyzes the prospects for the emergence of civil patriotism in Russia in the context of solidarity practices as a way to strengthen the state-civil identity and unity of all the nations in modern Russia. Given the existing differences in the development of patriotism and social solidarity in the West and in Russia, as well as the sociocultural foundations for the formation of civil patriotism in the context of solidarity practices, civil engagement and moral responsibility of citizens to the civil community are singled out as a determining condition Â